Menopause Is a Key Factor Influencing Postprandial Metabolism, Metabolic Health and Lifestyle: The ZOE PREDICT Study. (14th June 2022) - Bermingham, Kate; Linenberg, Inbar; Valdes, Ana; Hall, Wendy; Manson, JoAnn; Newson, Louise; Chan, Andrew; Kade, Kirstin; Franks, Paul; Wolf, Jonathan; Spector, Tim; Berry, Sarah
Abstract: Objectives: The menopause transition is associated with unfavourable alterations in metabolic and cardiovascular health. However, as an age-related biological event, it is difficult to untangle effects of age from menopause. Here, we investigate the impact of menopause on cardiometabolic health, lifestyle and diet in pre- and post-menopausal females and age-matched subgroups (including males) in the densely phenotyped ZOE PREDICT 1 cohort (NCT03479866). Methods: Demographic information, diet, cardiometabolic blood biomarkers and postprandial responses (lipid and glucose) to standardized test meals in clinic and free-living settings were assessed (n = 1002). Self-reported pre- ( n  = 366), peri- ( n  = 55) and post-menopausal ( n  = 207) females (aged 18–65 y) and an age-matched subgroup (aged 47–56 y) of males ( n  = 76), pre- ( n  = 83) and post-menopausal females ( n  = 64) were identified. Linear regression analysis assessed differences in cardiometabolic health, anthropometry, lifestyle and diet (adjusted for sex, age, BMI, menopausal hormonal treatment and smoking status). Results: Post-menopausal females had poorer fasting and postprandial blood measures (glucose, HbA1c, inflammation (GlycA), glucose2hiauc and insulin2hiauc ; by 6, 5, 4, 42 and 4% respectively) and sleep quality (12%) and higher sugar intakes (12%) compared with pre-menopausal females (p < 0·05 for all). In age-matched females, postprandial glycemia was significantly higher in post- versus pre-menopausal females (p < 0·05), including clinic postprandial glucose peak0-2h (7·6 ± 1·2  vs  7·2 ± 1·0),  glycemic variability (using a continuous glucose monitor (CGM)) (18 ± 4%  vs  16 ± 4%) and glucose2hiauc (CGM) following a standardized (typical UK/US nutrient composition) meal (13440 ± 5804 vs 12547 ± 5488). Compared to age-matched males, females (pre- and post-menopausal) had lower systolic blood pressure and ASCVD 10y risk (p < 0.05) and post-menopausal females only had worse glycemic variability (p < 0·001). Conclusions: In the largest, in-depth nutrition metabolic study of menopause to date, we demonstrate unfavourable links between menopause transition and postprandial glycemic responses, sleep and diet. This emphasises the value of incorporating menopause as a factor in the delivery of nutrition advice. Funding Sources: ZOE Ltd